ANALISIS USABILITY SISTEM ABSENSI ONLINE MENGGUNAKAN METODE SUS PADA SUDIN NAKERTRANSGI KEPULAUAN SERIBU - Muhammad Fathi Robbani Mutawakkilin; Ricki Sastra; Mohammad Aris (Jurnal Komunikasi, 2025)
This study aims to evaluate the level of usability of the online attendance system used at the Seribu Islands Manpower and Transmigration Sub-dept. using the System Usability Scale (SUS) method. The online attendance system is a digital solution that facilitates the process of recording employee attendance in real-time, but its effectiveness and ease of use need to be evaluated to ensure the system runs optimally. The research method used is quantitative with data collection through a Google Form-based questionnaire consisting of 10 questions using a 5-point Likert scale. The research sample of 45 respondents who are active employees at the Seribu Islands Manpower and Transmigration Sub-dept. was selected using the quota sampling technique. The collected data were analyzed using the SUS method with the help of Excel and SPSS software to test validity, reliability, and calculate the system usability score. The results showed a SUS score of 46.0 with a grade D, which indicates that the online attendance system has a fairly good level of usability but is not yet optimal. Based on these findings, it is concluded that further evaluation and development are needed to improve the ease of use and user satisfaction with this online attendance system. This study provides recommendations for improving the interface, user training, and periodic evaluations so that the system can function more effectively and efficiently